The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1161/01.res.47.4.620
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of human umbilical arteries. Studies on arteries from newborn children delivered by nonsmoking, white group D, diabetic mothers.

Abstract: The effect of diabetic metabolism on the human vascular wall studied, using the fetal cardiovascular system at birth as an experimental model. The ultrastructure of umbilical arteries from nine newborn children of nonsmoking diabetic mothers (White group D) was compared with that of 30 healthy nonsmokers. Intimal cushions, thickening of the basement membrane often with a multilaminal appearance, and glycogen accumulations, both in the cells of the intima and the media, were found. The cells of the intima were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…However, a slight, but non-significant increase in the inflammatory cells (lymphocytes) was found on the surface of umbilical venous endothelium in diabetic pregnancies. This is in line with previous findings of the injured endothelium in umbilical arteries in diabetic pregnancies: endothelial cell death and formation of a thick intima layer with myoendothelial cells, intimal cushions and loose junctions [12,24]. On the other hand, inflammatory cells may be the first signs of hyperglycaemia-induced endothelial injury due to increased oxidative stress [43] and reactive oxygen species [25] seen in fetoplacental vascular dysfunction in diabetic pregnancies.…”
Section: Infants Born To Diabetic Motherssupporting
confidence: 91%
See 2 more Smart Citations
“…However, a slight, but non-significant increase in the inflammatory cells (lymphocytes) was found on the surface of umbilical venous endothelium in diabetic pregnancies. This is in line with previous findings of the injured endothelium in umbilical arteries in diabetic pregnancies: endothelial cell death and formation of a thick intima layer with myoendothelial cells, intimal cushions and loose junctions [12,24]. On the other hand, inflammatory cells may be the first signs of hyperglycaemia-induced endothelial injury due to increased oxidative stress [43] and reactive oxygen species [25] seen in fetoplacental vascular dysfunction in diabetic pregnancies.…”
Section: Infants Born To Diabetic Motherssupporting
confidence: 91%
“…The umbilical cord cells possess a wide differentiation potential and plasticity while being exposed to various pregnancy-induced changes [11], and in accordance, the ultrastructure of human umbilical arteries is altered in diabetic pregnancies [12,13]. Further, the umbilical vein endothelial cells from diabetic pregnancies show increased gene expression and activity of endothelial nitric oxide synthase, indicating altered vascular reactivity [14].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In an electron-microscopic study, Asmussen [18] showed intimal cushions, thickening of basement membrane, often with a multilaminal appearance, and glycogen accumulations, both in the cells of the umbilical artery intima, and media of infants of nonsmoking, white group D diabetic mothers, but the correlation of these findings with clinical and laboratory data was not investigated. In order to prove the hypothesis that preclinical atherosclerosis begins in utero, we measured uIMT, puWT and ruWT by radiological and pathological techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is usually patent for some time after birth and may be used for exchange transfusions during early infancy [Moore, 1980]. Electron microscope studies of umbilical vasculature have focused mainly on intimal features occurring in normal and pathological cases, which arc present at birth [Asmussen, 1980;Las Heras and Haust, 1981], However, detailed electron miscroscopic developmental studies of umbilical vasculature from midgestation through early postnatal life have not been reported. In this study, the differences in cell fea tures between umbilical arteries and veins at different stages of developmental are evaluated, with special emphasis on lipid droplet formation.…”
Section: Introductionmentioning
confidence: 99%